DISTRIBUSI TIMBAL DALAM UDARA AKIBAT EMISI KENDARAAN BERMOTOR DI KAWASAN KAMPUS UGM YOGYAKARTA - Robo, Tamrin (Green Earth, 2012)
Recently, the increase of motor vehicle number in campus area of Gadjah Mada University Yogyakarta clearly affects air quality. This transportation vehicle was presumably become the source of air pollution such as lead distributed within air. This study is purposed to investigate correlation of motor vehicle density with lead concentration contaminating within air, correlation of land use form and lead concentration, and correlation of climate parameters (temperature, humidity, wind direction and velocity) towards lead concentration within air in Agro street, Colombo street, and Kesehatan street. Sampling was taken using purposive sampling method accorded to the distances from the road (<1 m, 100 m, 200 m and 300) in researchâs location. The sampling was taken by means of Low Volume Air Sampler then lead (Pb) is measured using Atomic Absorption Spectrophotometer (AAS). Data analysis was taken using quantitatively descriptive method.The result suggests that there is correlation between density of motor vehicle and lead (Pb) concentration within air. The highest density of motor vehicle was found in Agro street. Lead concentration distributed within air was relatively fluctuated accorded to the distance from road edge; the highest lead concentration was found in Colombo street (0.00395 Âµg/m3) with distance of < 1 m and the lowest was found in Agro street (0.0008 Âµg/m3) with distance of 200 m. Agro street is a road with more plants aside than those of Colombo street and Kesehatan street which very rare. The highest temperature of 37,8oC was found in Kesehatan street and the lowest was 29,5oC in Agro street. Besides, the highest humidity was found in Kesehatan street of 79,05% and the lowest was found in Colombo street of 60,95%. The highest wind velocity is found in Colombo street of 0,8 m/s and the lowest one was found in Agro street of 0,35 m/s. Lead concentration in these three locations, if it is correlated with quality standard of natural environment of 2 Âµg/m2, was categorized into low, i.e. below the quality standard allowed. Key words : Motor vehicle emission, air lead, air temperature, air humidity and wind velocity.